Clozapine rapid retitration in the community: an assertive approach can prevent admissions. (28th June 2018) - Nikolić, Nikola; Kilbride, Kevin; Preston, Patrick
SUMMARY: Rapid retitration of clozapine may be necessary to reduce the known high risk of mental state destabilisation in patients who have had a 48 h treatment break. It may carry a high risk of complications, including seizures and myocarditis. We reflect on the literature on standard and rapid retitration and present a case of rapid retitration in the community. In this case, of a 54-year-old homeless man with treatment-resistant schizophrenia and polysubstance misuse, we safely retitrated clozapine in a community setting four times during a 6-month period; each retitration was completed over 4 days. We used a specific protocol based on his psychiatric history. We are now more confident in delivering clozapine retitration to other patients, thus preventing unnecessary admissions. DECLARATION OF INTEREST: N. N. has received honoraria from Janssen Pharmaceuticals.